Impact of adverse effects to oral antidiabetics on adherence and quality of life in patients with type 2 diabetes. (24th June 2020) - Almeida, C; Rocha, C; Cruz, R
Abstract: Introduction Diabetes is a metabolic disorder with many comorbidities, microvascular and macrovascular complications. In Portugal the prevalence was 13, 3% which corresponds to 1 million Portuguese diagnosed, but the forecasts are for a big increase. The various therapeutic options currently available have been shown to be effective in controlling glycaemia and HbA1 levels. Adherence with this therapeutic is essential for optimization and control of chronic conditions. However, they present side effects that may compromise adherence to therapy and the quality of life of the patients. Objectives The objective of this study is to evaluate the impact of the adverse effects of oral antidiabetic medicines on patient's quality of life and adherence to therapy. Methodology We developed a cross-sectional study in a sample of 65 patients with type 2 diabetes recruited in several Portuguese pharmacies. Data collected through a questionnaire previously validated with MAT Scale and EQ-5D-3L questionnaire. Results In total, 36 men (55, 4%) and 29 women (44, 6%) participated in the study, the mean age was 65 years. 73, 8 % take oral medication and 92, 30% of people have high adherence. The adverse events with more impact in the patients' perception are "Discomfort in the genital area", "Dry mouth" and gastrointestinal events such as "Abdominal distention", "Flatulence" and "Constipation". The number of adverse events have a negative impact on patients' quality of life (rs=-0, 479; p≤0, 01). The satisfaction with the therapeutic regime is significantly associated with adherence (rs = 0, 348; p≤0, 01)and their quality of life (rs = 0, 316; p=0, 01). Conclusion We concluded that the adverse events have a negative impact on adherence and quality of life. The presence of adverse events, the type of medication and the therapeutic regimen are factors that negatively influence the patients' quality of life, especially in the polymedicated elderly people.